2013
DOI: 10.1186/1999-3110-54-38
|View full text |Cite
|
Sign up to set email alerts
|

Recircumscription of Begonia sect. Baryandra (Begoniaceae): evidence from molecular data

Abstract: BackgroundBegonia sect. Diploclinium is a ‘dust-bin’ section for species retaining pleisiomorphic characters and lacking novel synapomorphic characters used to delimit other Asian sections in Begonia. Part of this large and polymorphous section is transferred to Begonia sect. Baryandra in a move towards a more natural classification for the genus.ResultsPhylogenetic analysis of nuclear ribosomal ITS DNA sequences show a strongly supported monophyletic group containing Philippine and Bornean species previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 6 publications
4
36
0
Order By: Relevance
“…Diploclinium (Lindley ex R. Wight 1852: 9) A. de Candolle (1859: 129) from the Philippine were transferred to sect. Baryandra, based on the analysis of morphological features and molecular data (Rubite 2012;Rubite et al 2013). Among about 50 species in sect.…”
Section: Chromosome Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diploclinium (Lindley ex R. Wight 1852: 9) A. de Candolle (1859: 129) from the Philippine were transferred to sect. Baryandra, based on the analysis of morphological features and molecular data (Rubite 2012;Rubite et al 2013). Among about 50 species in sect.…”
Section: Chromosome Preparationsmentioning
confidence: 99%
“…Recently Philippine Begonia species are delimited into two sections: Baryandra A. de Candolle (1859: 122) and Petermannia (Klotzsch 1855: 74) A. de Candolle (1859: 128) (Rubite 2012;Rubite et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Petermannia (Klotzsch 1855: 74) A. de Candolle (1859, and sect. Platycentrum (Klotzsch 1855: 123) A. de Candolle (1859 (Rubite 2012, Rubite et al 2013. Begonia sect.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent comprehensive sectional classification of the genus is that by Doorenbos et al (1998 Diploclinium (Rubite et al, 2013). Doorenbos et al (1998) doubtfully placed Begonia calcarea in Begonia sect.…”
Section: Discussionmentioning
confidence: 99%
“…Sectional delimitation within this group needs to be revised. Rubite et al (2013) examined the rhizomatous Malesian Begonia sect. Diploclinium group, which has a centre of diversity in the Philippines, in detail and concluded that they were distinct from continental species of Begonia sect.…”
Section: Discussionmentioning
confidence: 99%